Penerapan Manajemen Strategis dalam Pendidikan Islam untuk Mendukung Dakwah Humanis di Nganjuk - A Wathon (ANWARUL, 2025)
The limited number of studies on the holistic application of strategic management in Islamic educational institutions, particularly those oriented toward strengthening dakwah humanis in specific regions such as Nganjuk forms the background of this research, given its urgency in shaping moderate and tolerant communities amidst contemporary socio-religious dynamics. This study aims to deeply analyze the implementation of strategic management in Islamic educational institutions in support of dakwah humanis, identify its enabling and inhibiting factors, and formulate an adaptive strategic model. A qualitative method with a multiple case study approach was employed, involving five Islamic educational institutions (madrasahs and pesantren) purposively selected based on their track records in innovation and community-based dakwah. Data were collected through in-depth interviews with institutional leaders, teachers, da’i, and community figures; participatory observation; and analysis of internal documents. Thematic analysis was applied through the stages of data reduction, data display, and conclusion drawing. The findings reveal variations in the implementation of strategic management; however, there is a general commitment to integrating humanistic values into the curriculum and dakwah programs through participatory planning and human resource development. The main conclusion emphasizes the critical role of transformational leadership and an adaptive organizational culture in enhancing the effectiveness of dakwah humanis within Islamic educational institutions. The implications of this research include contributions to the enrichment of the Islamic education management literature and practical recommendations for stakeholders, including local governments and the Ministry of Religious Affairs to strengthen managerial training, develop synergistic policies, and design measurable and sustainable community-based dakwah humanis models.